IMPLEMENTASI PERAN PUSAT INKUBASI BISNIS USAHA KECIL (PINBUK) DALAM UPAYA PENGEMBANGAN KOPSYAH BMT DI SULAWESI TENGAH - Nur wanita; Fadhliah Mubakkirah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
This research is based on the existence of PINBUK (Small Business Incubation Center) in general, especially Central Sulawesi PINBUK which can not be separated with the existence and development of sharia micro finance institution, especially Koperasi Syariah (Kopsyah) BMT in Central Sulawesi. The existence of Kopsyah BMT on one hand has access opportunities for small groups of people who find it difficult to access funds at formal financial institutions such as banks, amun on the other hand, not infrequently Kopsyah BMT, its existence is not going as expected. Therefore, this research tries to raise the problem: how is the implementation of PINBUK role in developing Kopsyah BMT in Central Sulawesi, and what factors are supporting and inhibiting the role of PINBUK in developing Kopsyah BMT in Central Sulawesi